High-viscosity asphalt double-layer SMA pavement layer structure and construction process thereof

By using a high-viscosity asphalt double-layer SMA pavement structure, modified asphalt and specific materials are used to form a continuous waterproof membrane and skeleton structure, which solves the problem of decreased mechanical properties caused by the poor viscosity of ordinary asphalt and improves the durability and stability of the pavement.

CN121047196AInactive Publication Date: 2025-12-02SHANDONG SHITONG HIGHWAY CONSTR CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511059580.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-30
Publication Date
2025-12-02
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In ordinary SMA pavement structures, the poor viscosity of ordinary asphalt leads to a decline in mechanical properties and affects the pavement life.

Method used

The structure employs a high-viscosity asphalt double-layer SMA pavement, comprising an upper pavement layer, a waterproof bonding layer, and a lower pavement layer. It utilizes modified asphalt, basalt fiber, porous ceramic microparticles, and other materials to form a continuous waterproof membrane and skeleton structure, enhancing adhesion, waterproofing, and load-bearing capacity.

Benefits of technology

It improves the mechanical strength, adhesion, water resistance and stability of the road surface, extends the service life of the road surface, and reduces the occurrence of defects such as cracks and ruts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005525329450000121
    Figure BDA0005525329450000121
Patent Text Reader

Abstract

The invention belongs to the technical field of steel bridge pavement, and particularly discloses a high-viscosity asphalt double-layer SMA pavement layer structure and a construction technology thereof. The high-viscosity asphalt double-layer SMA pavement layer structure comprises an upper pavement layer, a waterproof bonding layer and a lower pavement layer, the upper pavement layer is laid on the lower pavement layer, the upper pavement layer comprises fine aggregate, limestone powder, modified asphalt, basalt fibers and a Wenn glue mixture, the thickness of the upper pavement layer is 35-40 mm, and the thickness of the waterproof bonding layer is 10-20 mm. The waterproof bonding layer comprises modified asphalt, epoxy resin, a silane coupling agent, a curing agent, a curing accelerator, butadiene styrene rubber, a silane coupling agent and talcum powder, the thickness of the waterproof bonding layer is 0.5-1 mm, and the lower pavement layer comprises coarse aggregate, modified asphalt, acrylonitrile-butadiene-styrene copolymer, porous ceramic particles, rubber particles, calcium stearate and waterborne polyurethane. And the thickness of the lower paving layer is 10-15mm. Various raw materials are mixed, so that the strength and durability of the pavement layer structure are improved, and the service life of the pavement is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the technical field of steel bridge paving, and in particular to a high-viscosity asphalt double-layer SMA paving structure and its construction process. Background Technology

[0002] The bridge deck pavement is a crucial functional structure of a bridge. On one hand, it directly bears the loads of traffic and the deformation of the bridge beams, affecting driving comfort and safety. On the other hand, it plays a vital protective role, preventing rainwater infiltration and corrosion of the main bridge structure. Therefore, the bridge deck pavement directly impacts the overall operational quality and service level of the bridge, and even its service life.

[0003] SMA (Stone Mastic Asphalt) pavement structure is a high-performance asphalt pavement structure widely used in highway, urban expressway, and bridge paving projects. SMA pavement structures typically consist of asphalt, fiber stabilizers, mineral powder, and a small amount of fine aggregate, exhibiting good high-temperature stability, excellent rutting resistance, a porous skeleton structure, and superior skid resistance.

[0004] However, ordinary SMA pavement structure is only composed of ordinary asphalt, fiber stabilizer, mineral powder and fine aggregate. Ordinary asphalt has poor viscosity and is prone to poor adhesion to fine aggregate, which leads to a decrease in mechanical properties and thus affects the pavement life. Summary of the Invention

[0005] To address the issue of decreased mechanical properties caused by ordinary asphalt, this application provides a high-viscosity asphalt double-layer SMA pavement structure and its construction process.

[0006] This application provides a high-viscosity asphalt double-layer SMA pavement structure, which adopts the following technical solution: A high-viscosity asphalt double-layer SMA pavement structure includes an upper pavement layer, a waterproof bonding layer, and a lower pavement layer. The upper pavement layer is laid on top of the lower pavement layer. The upper pavement layer includes fine aggregate, limestone powder, modified asphalt, basalt fiber, and Wenlun rubber mixture, and has a thickness of 35-40 mm. The waterproof bonding layer includes modified asphalt, epoxy resin, silane coupling agent, curing agent, curing accelerator, styrene-butadiene rubber, and talc powder, and has a thickness of 0.5-1 mm. The lower pavement layer includes coarse aggregate, modified asphalt, acrylonitrile-butadiene-styrene copolymer, porous ceramic microparticles, rubber particles, calcium stearate, and waterborne polyurethane, and has a thickness of 10-15 mm.

[0007] By adopting the above technical solutions, in the upper pavement layer, fine aggregates form the basic skeleton of the upper pavement layer. The particles are interlocked, providing basic load-bearing capacity for the pavement. Limestone powder fills the gaps between the fine aggregates, making the mixture more compact and enhancing the overall stability of the pavement. Basalt fiber has high strength, high modulus, and good chemical stability. It is uniformly dispersed in the system, and through the interweaving and adsorption between the fibers, it enhances the structural stability and crack resistance of the pavement layer. Modified asphalt can firmly bond various aggregates together to form a whole mixture structure. Wernite rubber mixture improves the adhesion and high-temperature stability of the upper pavement layer, greatly enhancing the adhesion between limestone powder, basalt fiber, and fine aggregates, effectively preventing aggregates from falling off under vehicle loads and improving pavement durability.

[0008] In the waterproof bonding layer, modified asphalt provides excellent adhesion, ensuring a tight bond between the upper and lower pavement layers. It also forms a continuous waterproof membrane on the road surface, preventing rainwater and other moisture from penetrating the pavement structure and protecting the underlying structure from water damage. Epoxy resin exhibits excellent adhesion properties, bonding tightly with the materials of both upper and lower pavement layers, enhancing the adhesion between them, and making the entire pavement layer a unified whole, jointly bearing vehicle loads. The curing agent and curing accelerator promote the curing reaction of the epoxy resin, enabling it to form a bond with a certain strength and stability in a short time, enhancing the waterproof performance and chemical stability of the waterproof bonding layer. Styrene-butadiene rubber improves the flexibility and deformation resistance of the waterproof bonding layer, allowing it to adapt to road surface deformation under temperature changes and vehicle loads, preventing cracking of the waterproof layer, and improving the elasticity and impact resistance of the pavement layer. Talc powder adjusts the consistency and workability of the waterproof bonding layer, while also helping to improve the density and waterproof effect of the waterproof layer.

[0009] In the subpavement, coarse aggregate forms the skeletal structure. Its larger particle size and interlocking effectively distribute vehicle loads, providing good mechanical support and drainage performance, ensuring the pavement's load-bearing capacity and reducing water damage. Acrylonitrile-butadiene-styrene copolymer has excellent comprehensive properties, enhancing the subpavement's toughness and impact resistance, making the pavement less prone to damage under heavy vehicle loads. Modified asphalt better encapsulates aggregate particles, enhancing the bond between aggregates, improving the overall strength and stability of the mixture, and resisting vehicle loads. Porous ceramic microparticles have high strength and good permeability, improving the subpavement's drainage performance and, in conjunction with other components, increasing the pavement's mechanical strength. Rubber granules improve the subpavement's elasticity and fatigue resistance, enhance its sound absorption and skid resistance, while reducing its weight. Waterborne polyurethane has good water resistance and durability, ensuring the subpavement's stability during long-term use.

[0010] The basalt fibers in the upper pavement layer enhance the strength and toughness of the mixture, enabling it to withstand both vertical and horizontal vehicle loads. The modified asphalt in the waterproof bonding layer forms a continuous waterproof membrane, effectively preventing moisture penetration into the pavement structure, protecting the lower pavement and base course from water damage, and extending the pavement's service life. The coarse aggregate skeleton and acrylonitrile-butadiene-styrene copolymer in the lower pavement layer improve the structure's load-bearing capacity and deformation resistance. Under repeated vehicle compaction, the entire pavement layer maintains good integrity, reducing the occurrence of cracks, rutting, and other defects.

[0011] Preferably, the upper paving layer comprises 120-130 parts fine aggregate, 12-15 parts limestone powder, 3-5 parts basalt fiber, 16-20 parts modified asphalt, and 25-30 parts Wenlun rubber mixture; the waterproof bonding layer comprises 50-60 parts modified asphalt, 15-18 parts epoxy resin, 1-2 parts silane coupling agent, 3-4 parts curing agent, 0.5-0.8 parts curing accelerator, 3-6 parts styrene-butadiene rubber, and 4-7 parts talc powder; and the lower paving layer comprises 150-160 parts coarse aggregate, 10-15 parts modified asphalt, 30-40 parts acrylonitrile-butadiene-styrene copolymer, 20-23 parts porous ceramic microparticles, 6-10 parts rubber granules, 8-12 parts calcium stearate, and 13-16 parts waterborne polyurethane.

[0012] By adopting the above technical solution, the amount range of raw materials for each layer of the upper pavement layer, waterproof bonding layer, and lower pavement layer is further limited. The resulting high-viscosity modified asphalt double-layer SMA pavement structure has good mechanical strength, adhesion, waterproofness and pavement stability. The combination of each component improves the pavement durability.

[0013] Preferably, the preparation method of the Wenlun rubber compound includes the following steps: (1) Disperse Wenlun collagen powder in deionized water, add magnesium aluminum silicate, nano titanium dioxide and sodium hydroxide solution, stir at 35-40℃ for 20-25 min, dry, grind to obtain pretreated Wenlun collagen. (2) Disperse the coconut shell mixture in deionized water, add the pretreated Wenlun gum, ferrous sulfate solution and soybean gum from step (1), stir at 50-55℃ for 1-2 hours, and dry to obtain Wenlun gum mixture.

[0014] By employing the above technical solution, magnesium aluminum silicate acts as a thickener, improving the suspension and stability of the system, thus ensuring stable dispersion of the Wenlun adhesive. Simultaneously, it prevents the sedimentation of nano-titanium dioxide, resulting in a uniform and stable system. Nano-titanium dioxide possesses excellent optical properties, mechanical strength, and certain antibacterial properties, allowing it to be embedded within the Wenlun adhesive's structural structure and enhancing its corresponding performance. Sodium hydroxide solution adjusts the pH value of the system, promoting the dispersion of the Wenlun adhesive and contributing to improved reactivity in subsequent applications.

[0015] The coconut shell mixture possesses a porous structure, good adsorption, wear resistance, and toughness. When mixed with pretreated Werlen gum, ferrous sulfate solution, and soybean gum, the pretreated Werlen gum exhibits good adhesion. The ferrous sulfate solution promotes the interaction between the pretreated Werlen gum and the components in the coconut shell mixture, forming a cross-linked network structure, which improves the system's antioxidant properties, mechanical properties, and stability. Soybean gum increases the system's viscosity and water retention, while the hydroxyl groups in soybean gum undergo esterification with the carboxyl groups in Werlen gum, thereby enhancing the composite material's mechanical properties, adhesion, and stability. Subsequently, when applied to the upper paving layer, it improves the adhesion between the various components in the upper paving layer, enhances the overall strength of the system, and improves its durability, crack resistance, wear resistance, and mechanical properties.

[0016] Preferably, the mass ratio of the Wenlun collagen powder, coconut shell mixture and soy gum is 1:0.6-0.7:0.2-0.3.

[0017] By adopting the above technical solution and further limiting the mass ratio of Werlen gum powder, coconut shell mixture, and soybean gum within a certain range, the resulting Werlen gum mixture exhibits superior comprehensive performance. Werlen gum possesses strong adhesion, water retention, and film-forming properties. The coconut shell mixture has a certain porous structure, high mechanical strength, and good wear resistance, enabling it to disperse within the Werlen gum system and enhance its mechanical properties and wear resistance. Soybean gum has excellent bonding properties. Werlen gum powder and soybean gum form an organic cementitious network, encapsulating the coconut shell mixture and strengthening the bond between aggregates, forming a "rigid-flexible" composite structure. In road paving, Werlen gum powder enhances the system's adhesion and flexibility, the coconut shell mixture provides mechanical support and improves drainage performance, and soybean gum further enhances adhesion and flexibility, thereby improving the overall performance and service life of the road. This significantly improves the paving layer's adhesion, flexibility, wear resistance, durability, and drainage performance.

[0018] Preferably, the method for preparing the coconut shell mixture includes the following steps: crushing coconut shells, drying them, dispersing them in citric acid, stirring for 10-15 minutes, washing them with water, dispersing them again in deionized water, adding silane coupling agent-modified chitosan microspheres, microporous activated carbon, and rosin extract, stirring at 160-180 r / min for 1-2 hours at room temperature, drying them, ball milling them, and sieving them to obtain the coconut shell mixture; The method for preparing chitosan microspheres modified with silane coupling agent includes the following steps: dispersing chitosan in acetic acid solution, adding epichlorohydrin and sodium tripolyphosphate to obtain a pre-crosslinked material, dispersing the pre-crosslinked material in silicone oil, adding an emulsifier, spray drying, washing with n-hexane to obtain microspheres, dispersing the microspheres in an aqueous solution of silane coupling agent, stirring for 1-2 hours, filtering, and obtaining chitosan microspheres modified with silane coupling agent.

[0019] By employing the above technical solutions, citric acid reacts chemically with certain components in coconut shells (such as lignin and cellulose), improving the surface properties of the coconut shells and increasing their hydrophilicity and reactivity, which facilitates subsequent mixing of coconut shells with other components. Chitosan microspheres modified with silane coupling agents possess good biocompatibility and mechanical properties, enhancing the strength and stability of the coconut shell mixture. Microporous activated carbon, with its high specific surface area and adsorption capacity, improves the adsorption and filtration performance of the coconut shell mixture. The silane coupling agent-modified chitosan microspheres can adsorb within the microporous activated carbon and coconut shell structure. Rosin extract, with its good adhesion and waterproof properties, enhances the adhesion and water resistance of the mixture, resulting in a tight bond between the silane coupling agent-modified chitosan microspheres, microporous activated carbon, and coconut shell. The resulting coconut shell mixture exhibits good mechanical properties, adhesion, and air permeability, subsequently improving the performance of the Wenlun adhesive and thus enhancing the overall performance of the upper paving layer.

[0020] In the preparation method of chitosan microspheres modified with silane coupling agents, epichlorohydrin undergoes a cross-linking reaction with the amino groups in chitosan to form a cross-linked network structure. Sodium tripolyphosphate further enhances the cross-linking effect and improves the mechanical properties of chitosan. Silicone oil, as a dispersion medium, prevents the microspheres from sticking together during spray drying, resulting in uniform microspheres. Chitosan microspheres are obtained by spray drying, and the surface of the chitosan microspheres is modified with a silane coupling agent to increase their binding ability with inorganic materials, thereby improving the mechanical properties and stability of the microspheres. Through cross-linking reaction, spray drying, and surface modification, microspheres with high mechanical properties and good surface activity are prepared, which can subsequently improve the corresponding properties of coconut shell mixtures.

[0021] Preferably, the method for preparing the porous ceramic microparticles includes the following steps: (1) Ceramic powder, nano-calcium carbonate and nano-clay are dispersed in deionized water to obtain a slurry, which is then spray-dried to obtain porous particles; (2) Disperse starch-coated lignin particles in butanone, add the porous particles, polytetrafluoroethylene powder and alicyclic polyamine from step (1), stir at 70-75℃ for 1-2 hours, filter, wash with water, and dry to obtain porous ceramic microparticles.

[0022] By employing the above technical solution, the ceramic exhibits high strength, high hardness, and good wear resistance. The fine, small-particle-size calcium carbonate nanoparticles, with their large specific surface area, can fill the tiny gaps between ceramic powder and other particles, making the porous particle structure more dense and uniform, thus improving its performance. The nano-clay possesses excellent adsorption and ion exchange properties, capable of adsorbing ceramic powder and nano-calcium carbonate, increasing the viscosity and stability of the slurry. Spray drying of the slurry yields porous particles. During spray drying, the solvents in the nano-calcium carbonate and nano-clay evaporate, forming pores that increase the pore structure and mechanical strength of the system, as well as the specific surface area and reactivity, which is beneficial for subsequent processing of the porous particles.

[0023] Starch-coated lignin particles possess certain flexibility, crack resistance, and adhesiveness. When mixed with porous particles, polytetrafluoroethylene powder, and alicyclic polyamines, they can adhere to the porous particles, be loaded into the porous particle structure, improve the toughness and crack resistance of the porous particles, and play a role in bonding and toughening.

[0024] Polytetrafluoroethylene (PTFE) powder provides high-temperature resistance and chemical stability, forming a coating layer that can encapsulate starch, lignin particles, and porous particles, improving the wear resistance, chemical stability, and corrosion resistance of porous ceramic microparticles. Alicyclic polyamines act as crosslinking and curing agents, enabling PTFE and other substances to solidify and mold, ensuring uniform dispersion of components and firmly binding them together to form porous ceramic microparticles with certain strength and stability. Subsequent applications in paving structures enhance their mechanical strength, wear resistance, and adhesion, extending their durability.

[0025] Preferably, the mass ratio of the ceramic powder, starch-coated lignin particles, and polytetrafluoroethylene powder is 1:0.4-0.5:0.08-0.09.

[0026] By adopting the above technical solution and further limiting the mass ratio of ceramic powder, starch-coated lignin particles, and polytetrafluoroethylene powder within a certain range, the resulting porous ceramic microparticles exhibit better comprehensive performance. The ceramic powder possesses high strength, high hardness, and good wear resistance, resulting in a more robust paving structure capable of withstanding heavier traffic loads and long-term wear.

[0027] Starch-coated lignin granules: Starch possesses adhesiveness, flexibility, and crack resistance, enabling it to adsorb within the pores of ceramic powder particles, thus enhancing their corresponding properties. Polytetrafluoroethylene (PTFE) powder partially melts and coats the ceramic particles, forming a "core-shell" structure. This increases the adhesion between the ceramic powder and the starch-coated lignin granules, further improving the mechanical strength, adhesion, and toughness of the ceramic powder. When subsequently applied to paving structures, the resulting granules act as a binder and toughener, improving the material's toughness and crack resistance, reducing crack formation, enhancing pavement durability, and increasing the overall strength and load-bearing capacity of the paving structure. This allows it to withstand greater vehicle loads and resist pavement deformation and damage.

[0028] Preferably, the method for preparing the starch-coated lignin particles includes the following steps: dispersing lignin in ethylene glycol, adding disodium lauryl sulfosuccinate monoester and carbon nanotubes, and then subjecting the mixture to ultrasonic treatment and freeze-drying to obtain lignin particles; Lignin particles were dispersed in a starch aqueous solution, sodium trimetaphosphate and sodium hydroxyphosphate were added, and the mixture was stirred at 75-80℃ for 30-35 minutes and then dried to obtain starch-coated lignin particles.

[0029] By adopting the above technical solution, carbon nanotubes have unique mechanical and wear-resistant properties, and can be loaded on the surface of lignin particles to enhance the strength of lignin particles; disodium lauryl sulfonate monoester reduces interfacial tension, allowing carbon nanotubes to be better dispersed in the system, while also contributing to the formation and stabilization of lignin particles, thus enabling better bonding between lignin and carbon nanotubes.

[0030] Lignin particles were dispersed in a starch aqueous solution, and sodium trimetaphosphate and sodium hydroxide were added. The starch and lignin particles were thoroughly mixed and a cross-linking reaction occurred, allowing the starch to uniformly coat the surface of the lignin particles. Sodium trimetaphosphate and sodium hydroxide acted as cross-linking agents, reacting with the starch and lignin to form a cross-linked network structure, promoting the coating and cross-linking of starch on the surface of the lignin particles, and forming a stable starch coating layer. The resulting starch-coated lignin particles exhibited good mechanical properties, adhesion, and abrasion resistance.

[0031] Preferably, the fine aggregate is river sand with a particle size of 5-8 mm, and the coarse aggregate is basalt crushed stone with a particle size of 14-18 mm.

[0032] By adopting the above technical solutions, river sand can fill the gaps between particles, making the paving material structure more compact and improving the overall density and compressive strength. Basalt crushed stone, as coarse aggregate, forms the skeleton structure in the paving structure, bearing the main load and resisting the pressure and impact generated by vehicle traffic, preventing excessive deformation and damage to the road surface.

[0033] Secondly, this application also provides a construction process for a high-viscosity modified asphalt double-layer SMA pavement structure, including the following steps: (1) Mix fine aggregate, limestone powder, modified asphalt, basalt fiber and Wenlun rubber mixture to obtain the upper paving mixture; (2) Mix modified asphalt, epoxy resin, silane coupling agent, curing agent, curing accelerator, styrene-butadiene rubber and talc to obtain a waterproof adhesive; (3) Mix coarse aggregate, acrylonitrile-butadiene-styrene copolymer, modified asphalt, porous ceramic microparticles, rubber particles, calcium stearate and waterborne polyurethane to obtain the underlayment mixture; (4) Lay the lower mixture flat and compact it, then apply waterproof adhesive, then lay the upper mixture flat and compact it, and cure for 20-24 hours to obtain a high viscosity modified asphalt double-layer SMA pavement structure.

[0034] By adopting the above technical solutions and construction processes, the operation is simple and the process time is short, which helps to improve the mechanical and waterproof performance of the high-viscosity asphalt double-layer SMA pavement structure. The resulting high-viscosity asphalt double-layer SMA pavement structure has good durability.

[0035] In summary, this application has the following beneficial effects: 1. In this application, the basalt fiber in the upper pavement layer enhances the strength and toughness of the mixture, enabling it to withstand the vertical and horizontal loads of vehicles; the coarse aggregate skeleton and acrylonitrile-butadiene-styrene copolymer and other materials in the lower pavement layer improve the load-bearing capacity and deformation resistance of the structure.

[0036] 2. The continuous waterproof membrane formed by the modified asphalt in the waterproof bonding layer of this application can effectively prevent water from penetrating into the interior of the pavement structure, protect the underlayment and base layer from water damage, and extend the service life of the pavement.

[0037] 3. Under repeated vehicle compaction, the entire pavement layer can maintain good integrity, reducing the occurrence of defects such as cracks and ruts, and improving the service life of the road surface. Detailed Implementation

[0038] The present application will be further described in detail below with reference to the embodiments.

[0039] The raw materials used in the examples and comparative examples are all commercially available.

[0040] Example of the preparation of Wenlun adhesive compound Preparation Example 1-1 The preparation method of Wenlun rubber compound includes the following steps: (1) Disperse 35kg of Wenlun collagen powder in 60L of deionized water, add 2kg of magnesium aluminum silicate, 10kg of nano titanium dioxide and 3L of sodium hydroxide solution with a mass fraction of 10%, stir at 38℃ for 23min, dry, grind to obtain pretreated Wenlun collagen. (2) Disperse the coconut shell mixture in 120L of deionized water, add the pretreated Wenlun gum from step (1), 8kg of 6% ferrous sulfate solution, and soybean gum, stir at 54℃ for 1.5h, and dry to obtain the Wenlun gum mixture.

[0041] The mass ratio of Wenlun collagen powder, coconut shell mixture, and soy gum is 1:0.7:0.3.

[0042] The preparation method of the coconut shell mixture includes the following steps: 50 kg of coconut shells are crushed, dried, dispersed in 80 L of citric acid, stirred for 12 min, washed with water, and then dispersed in 100 L of deionized water. 20 kg of silane coupling agent-modified chitosan microspheres, 8 kg of microporous activated carbon, and 5 kg of rosin extract are added. The mixture is stirred at 170 r / min at room temperature for 1.6 h, dried, ball-milled, and passed through an 80 mesh sieve to obtain the coconut shell mixture. The preparation method of chitosan microspheres modified with silane coupling agent includes the following steps: 23 kg of chitosan is dispersed in 45 L of 10% acetic acid solution, 5 kg of epichlorohydrin and 7 kg of sodium tripolyphosphate are added to obtain a pre-crosslinked material, the pre-crosslinked material is dispersed in 70 L of silicone oil, 0.5 kg of Span 80 is added, homogenized (20 MPa, 3 cycles), spray dried (inlet air temperature 150℃, outlet air temperature 80℃, pressure nozzle, 15 MPa, droplet size 6-10 μm), washed with n-hexane to obtain microspheres, the microspheres are dispersed in 55 L of 3% silane coupling agent aqueous solution, stirred for 1.6 h, filtered to obtain chitosan microspheres modified with silane coupling agent.

[0043] Preparation Examples 1-2 The difference from preparation example 1-1 is that in step (2), the coconut shell mixture is not added.

[0044] Preparation Examples 1-3 The difference from preparation example 1-1 is that soybean gum is not added in step (2).

[0045] Preparation Examples 1-4 The difference from Preparation Example 1-1 is that the mass ratio of Wenlun collagen powder, coconut shell mixture and soybean gum is 1:0.6:0.2.

[0046] Preparation Examples 1-5 The difference from Preparation Example 1-1 is that the mass ratio of Wenlun collagen powder, coconut shell mixture and soybean gum is 1:0.1:0.9.

[0047] Preparation Examples 1-6 The difference from Preparation Example 1-1 is that the preparation method of the coconut shell mixture does not include chitosan microspheres modified with silane coupling agents.

[0048] Preparation Examples 1-7 The difference from Preparation Example 1-1 is that rosin extract is not added in the preparation method of the coconut shell mixture.

[0049] Example of preparation of porous ceramic microparticles Preparation Example 2-1 The method for preparing porous ceramic microparticles includes the following steps: (1) 28 kg of ceramic powder, 3 kg of nano calcium carbonate and 5 kg of nano clay (sepiolite powder) were dispersed in 40 L of deionized water to obtain a slurry, which was then spray-dried (inlet air temperature 220℃, outlet air temperature 100℃, atomization speed 18000 rpm, droplet size 10-20 μm, feed rate 8 L / h) to obtain porous particles; (2) Disperse starch-coated lignin particles in 50 kg of butanone, add the porous particles from step (1), polytetrafluoroethylene powder, and 2 kg of alicyclic polyamine, stir at 73°C for 1.5 h, filter, wash with water, and dry to obtain porous ceramic microparticles.

[0050] The mass ratio of ceramic powder, starch-coated lignin particles, and polytetrafluoroethylene powder is 1:0.4:0.08.

[0051] The preparation method of starch-coated lignin particles includes the following steps: 18 kg of lignin is dispersed in 35 L of ethylene glycol, 2 kg of disodium lauryl sulfosuccinate monoester and 6 kg of carbon nanotubes are added, and the mixture is subjected to ultrasonic treatment and freeze drying to obtain lignin particles. Lignin particles were dispersed in 35 L of a 5% starch aqueous solution, and 0.8 kg of sodium trimetaphosphate and 0.9 kg of sodium hydroxyphosphate were added. The mixture was stirred at 78 °C for 32 min and then dried to obtain starch-coated lignin particles.

[0052] Preparation Example 2-2 The difference from Preparation Example 2-1 is that in step (2), starch-coated lignin particles are not added.

[0053] Preparation Examples 2-3 The difference from preparation example 2-1 is that in step (2), polytetrafluoroethylene powder is not added.

[0054] Preparation Examples 2-4 The difference from Preparation Example 2-1 is that the mass ratio of ceramic powder, starch-coated lignin particles and polytetrafluoroethylene powder is 1:0.5:0.09.

[0055] Preparation Examples 2-5 The difference from Preparation Example 2-1 is that the mass ratio of ceramic powder, starch-coated lignin particles and polytetrafluoroethylene powder is 1:0.08:0.6.

[0056] Preparation Examples 2-6 The difference from Preparation Example 2-1 is that carbon nanotubes are not added in the preparation method of starch-coated lignin particles.

[0057] Preparation Examples 2-7 The difference from Preparation Example 2-1 is that starch is not added in the preparation method of starch-coated lignin particles. Example

[0058] Example 1 A high-viscosity asphalt double-layer SMA pavement structure includes an upper pavement layer, a waterproof adhesive layer, and a lower pavement layer. The upper pavement layer is laid on top of the lower pavement layer. The upper pavement layer has a thickness of 35 mm, the waterproof adhesive layer has a thickness of 0.5 mm, and the lower pavement layer has a thickness of 10 mm.

[0059] The upper paving layer includes 120 kg of fine aggregate, 12 kg of limestone powder, 3 kg of basalt fiber, 16 kg of modified asphalt, and 25 kg of Wenlun rubber mixture. The waterproof bonding layer includes 50 kg of modified asphalt, 15 kg of epoxy resin, 1 kg of silane coupling agent KH560, 3 kg of curing agent (polyetheramine curing agent), 0.5 kg of curing accelerator (2,4,6-tris(dimethylaminomethyl)phenol), 3 kg of styrene-butadiene rubber, and 4 kg of talc. The lower paving layer includes 150 kg of coarse aggregate, 10 kg of modified asphalt, 30 kg of acrylonitrile-butadiene-styrene copolymer, 23 kg of porous ceramic microparticles, 6 kg of rubber granules, 8 kg of calcium stearate, and 13 kg of waterborne polyurethane.

[0060] The modified bitumen was purchased from Guangdong Shuanghong Waterproof and Thermal Insulation Engineering Co., Ltd.

[0061] The Wenlun adhesive mixture was prepared using Preparation Example 1-1. The preparation method of porous ceramic microparticles includes the following steps: 28 kg of ceramic powder, 3 kg of nano-calcium carbonate and 5 kg of nano-clay (sepiolite powder) are dispersed in 40 L of deionized water to obtain a slurry, which is then spray-dried (inlet air temperature 220℃, outlet air temperature 100℃, atomization speed 18000 rpm, droplet size 10-20 μm, feed rate 8 L / h) to obtain porous ceramic microparticles.

[0062] The fine aggregate is river sand with a particle size of 5-8mm, and the coarse aggregate is basalt crushed stone with a particle size of 14-18mm.

[0063] A construction method for a high-viscosity asphalt double-layer SMA pavement structure includes the following steps: (1) Mix fine aggregate, limestone powder, modified asphalt, basalt fiber and Wenlun rubber mixture evenly to obtain the upper paving mixture; (2) Mix the modified asphalt, epoxy resin, silane coupling agent, curing agent, curing accelerator, styrene-butadiene rubber and talc powder evenly to obtain a waterproof adhesive. (3) Mix coarse aggregate, acrylonitrile-butadiene-styrene copolymer, modified asphalt, porous ceramic microparticles, rubber particles, calcium stearate and waterborne polyurethane evenly to obtain the underlay mixture; (4) Lay the lower mixture flat and compact it, then apply waterproof adhesive, let it stand for 6 hours, then lay the upper mixture flat and compact it, and cure it for 24 hours to obtain a high viscosity asphalt double-layer SMA pavement structure.

[0064] Example 2 A high-viscosity asphalt double-layer SMA pavement structure differs from Example 1 in that it includes an upper pavement layer, a waterproof adhesive layer, and a lower pavement layer. The upper pavement layer is laid on top of the lower pavement layer. The upper pavement layer has a thickness of 40 mm, the waterproof adhesive layer has a thickness of 1 mm, and the lower pavement layer has a thickness of 15 mm.

[0065] The upper paving layer consists of 130 kg of fine aggregate, 15 kg of limestone powder, 5 kg of basalt fiber, 20 kg of modified asphalt, and 30 kg of Wenlun rubber mixture. The waterproof bonding layer consists of 60 kg of modified asphalt, 18 kg of epoxy resin, 2 kg of silane coupling agent KH560, 4 kg of curing agent, 0.8 kg of curing accelerator, 6 kg of styrene-butadiene rubber, and 7 kg of talc. The lower paving layer consists of 160 kg of coarse aggregate, 15 kg of modified asphalt, 40 kg of acrylonitrile-butadiene-styrene copolymer, 20 kg of porous ceramic microparticles, 10 kg of rubber granules, 12 kg of calcium stearate, and 16 kg of waterborne polyurethane.

[0066] Example 3 A high-viscosity asphalt double-layer SMA pavement structure differs from Example 1 in that the Wenlun rubber mixture is prepared using Preparation Examples 1-2.

[0067] Example 4 A high-viscosity asphalt double-layer SMA pavement structure differs from Example 1 in that the Wenlun rubber mixture is prepared using Preparation Examples 1-3.

[0068] Example 5 A high-viscosity asphalt double-layer SMA pavement structure differs from Example 1 in that the Wenlun rubber mixture is prepared using Preparation Examples 1-4.

[0069] Example 6 A high-viscosity asphalt double-layer SMA pavement structure differs from Example 1 in that the Wenlun rubber mixture is prepared using Preparation Examples 1-5.

[0070] Example 7 A high-viscosity asphalt double-layer SMA pavement structure differs from Example 1 in that the Wenlun rubber mixture is prepared using Preparation Examples 1-6.

[0071] Example 8 A high-viscosity asphalt double-layer SMA pavement structure differs from Example 1 in that the Wenlun rubber mixture is prepared using Preparation Examples 1-7.

[0072] Example 9 A high-viscosity asphalt double-layer SMA pavement structure differs from Example 1 in that the porous ceramic microparticles are prepared using Preparation Example 2-1.

[0073] Example 10 A high-viscosity asphalt double-layer SMA pavement structure differs from Example 9 in that the porous ceramic microparticles are prepared using Preparation Example 2-2.

[0074] Example 11 A high-viscosity asphalt double-layer SMA pavement structure differs from Example 9 in that the porous ceramic microparticles are prepared using Preparation Examples 2-3.

[0075] Example 12 A high-viscosity asphalt double-layer SMA pavement structure differs from Example 9 in that the porous ceramic microparticles are prepared using Preparation Examples 2-4.

[0076] Example 13 A high-viscosity asphalt double-layer SMA pavement structure differs from Example 9 in that the porous ceramic microparticles are prepared using Preparation Examples 2-5.

[0077] Example 14 A high-viscosity asphalt double-layer SMA pavement structure differs from Example 9 in that the porous ceramic microparticles are prepared using Preparation Examples 2-6.

[0078] Example 15 A high-viscosity asphalt double-layer SMA pavement structure differs from Example 9 in that the porous ceramic microparticles are prepared using Preparation Examples 2-7.

[0079] Comparative Example Comparative Example 1 A high-viscosity asphalt double-layer SMA pavement structure differs from Example 1 in that it does not include Wenlun rubber mixture.

[0080] Comparative Example 2 A high-viscosity asphalt double-layer SMA pavement structure differs from Example 1 in that it does not contain porous ceramic microparticles.

[0081] Performance testing The high-viscosity asphalt double-layer SMA pavement structures prepared in Examples 1-15 and Comparative Examples 1-2 were subjected to performance tests. The compressive strength was tested according to the "Test Method for Strength of Cement Mortar (ISO Method)" (GB / T 17671-1999), the flexural strength was tested according to GB / T 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete", the abrasion resistance of the surface layer was tested according to T0567-2005 "Test Method for Abrasion Resistance of Cement Concrete", and the dynamic stability of the structure was tested according to T0719-2011 "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering". The test results are shown in Table 1.

[0082] Table 1 Test data for the examples and comparative examples As can be seen from Table 1, the high-viscosity asphalt double-layer SMA pavement structure prepared in Examples 1-2 of this application has good mechanical properties, wear resistance, and stability. Among them, the compressive strength of Example 1 is 38 MPa, the flexural strength is 7.6 MPa, and the surface layer wear resistance is 1.23 kg / m². 2 The dynamic stability is 6853 cycles / mm. It is evident that the high-viscosity asphalt double-layer SMA pavement structure prepared in this application possesses superior compressive strength, flexural strength, abrasion resistance, and stability, resulting in high durability and good construction performance for the SMA pavement structure.

[0083] In Examples 3-4, the preparation methods of Wernbear rubber mixtures did not include coconut shell mixture or soybean gum, respectively. In Examples 5-6, the mass ratio of Wernbear rubber powder, coconut shell mixture, and soybean gum was changed. As shown in Table 1, the test results of compressive strength, flexural strength, surface abrasion resistance, and dynamic stability of Examples 3-4 were significantly worse than those of Examples 1-2 and Example 5. The test results of the corresponding properties of Example 6 were better than those of Examples 3-4, but worse than those of Examples 1-2 and Example 5. This indicates that the coconut shell mixture can be dispersed in the Wernbear rubber system, increasing the mechanical properties and abrasion resistance of the Wernbear rubber system. The Wernbear rubber powder and soybean gum form an organic cementitious network, which encapsulates the coconut shell mixture and enhances the adhesion between aggregates. In road paving, this significantly improves the paving layer in terms of adhesion, flexibility, abrasion resistance, and durability.

[0084] In the preparation methods of coconut shell mixtures in Examples 7-8, chitosan microspheres modified with silane coupling agents and rosin extract were not added respectively. Table 1 shows that the compressive strength, flexural strength, surface abrasion resistance, and dynamic stability of Examples 7-8 were significantly worse than those of Examples 1-2, but better than Example 2. This indicates that the chitosan microspheres modified with silane coupling agents can be adsorbed into the microporous activated carbon and coconut shell structure. The rosin extract has good adhesion and waterproof properties, enhancing the adhesion and water resistance of the mixture. This results in a tight bond between the chitosan microspheres, microporous activated carbon, and coconut shell, leading to a coconut shell mixture with good mechanical properties, adhesion, and air permeability. This improves the corresponding properties of the Wenlun adhesive, thereby enhancing the overall performance of the upper paving layer.

[0085] Example 9 has a compressive strength of 49 MPa, a flexural strength of 9.8 MPa, and a surface abrasion resistance of 0.13 kg / m². 2 The dynamic stability is 6978 cycles / mm. It is evident that the porous ceramic microparticles prepared in this application possess excellent mechanical properties, wear resistance, and stability. Their subsequent application in paving structures can improve the mechanical strength, wear resistance, and adhesion of the paving structure, thereby extending its durability.

[0086] In Examples 10-11, the preparation methods of porous ceramic microparticles did not include starch-coated lignin particles or polytetrafluoroethylene (PTFE) powder. In Examples 12-13, the mass ratio of ceramic powder, starch-coated lignin particles, and PTFE powder was varied. Table 1 shows that the test results for compressive strength, flexural strength, surface abrasion resistance, and dynamic stability of Examples 10-11 were significantly worse than those of Examples 9 and 12, but better than Examples 1-2. The test results for the corresponding properties of Example 13 were better than those of Examples 10-11, but worse than those of Examples 9 and 12. This indicates that starch-coated lignin particles possess adhesiveness, flexibility, and crack resistance, and can be adsorbed into the pores of ceramic powder particles. The PTFE powder partially melts and coats the ceramic particles, forming a "core-shell" structure, increasing the adhesion between the ceramic powder and the starch-coated lignin particles, improving the mechanical strength, adhesion, and toughness of the ceramic powder, and subsequently improving the overall strength and load-bearing capacity of the paving structure, resisting pavement deformation and damage.

[0087] In Examples 14-15, the preparation methods of starch-coated lignin particles did not include carbon nanotubes or starch. As shown in Table 1, the compressive strength, flexural strength, surface abrasion resistance, and dynamic stability of Examples 14-15 were significantly worse than those of Example 9, but better than those of Examples 1-2. This indicates that carbon nanotubes possess unique mechanical and abrasion-resistant properties, enabling them to be loaded onto the surface of lignin particles and enhance their strength. The thorough mixing and cross-linking of starch with the lignin particles allows for uniform coating of the starch onto the lignin particle surface. The resulting starch-coated lignin particles exhibit good mechanical properties, adhesion, and abrasion resistance, thus improving the overall performance of the paving structure.

[0088] Comparative Examples 1-2 were tested without the addition of Wenlun rubber mixture and porous ceramic microparticles, respectively. As shown in Table 1, the compressive strength, flexural strength, surface abrasion resistance, and dynamic stability of Comparative Examples 1-2 were significantly worse than those of Examples 1-2. This indicates that the Wenlun rubber mixture improves the adhesion and high-temperature stability of the upper pavement layer, greatly enhancing the adhesion between limestone powder, basalt fiber, and fine aggregates, effectively preventing aggregates from falling off under vehicle loads and improving pavement durability. The porous ceramic microparticles have high strength and good permeability, and when combined with other components, they improve the mechanical strength of the pavement.

[0089] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A high-viscosity asphalt double-layer SMA pavement structure, characterized in that, The system comprises an upper paving layer, a waterproof bonding layer, and a lower paving layer. The upper paving layer is laid on top of the lower paving layer and includes fine aggregate, limestone powder, modified asphalt, basalt fiber, and Wenlun rubber mixture. The thickness of the upper paving layer is 35-40mm. The waterproof bonding layer includes modified asphalt, epoxy resin, silane coupling agent, curing agent, curing accelerator, styrene-butadiene rubber, and talc powder. The thickness of the waterproof bonding layer is 0.5-1mm. The lower paving layer includes coarse aggregate, modified asphalt, acrylonitrile-butadiene-styrene copolymer, porous ceramic microparticles, rubber particles, calcium stearate, and waterborne polyurethane. The thickness of the lower paving layer is 10-15mm.

2. The high-viscosity asphalt double-layer SMA pavement structure according to claim 1, characterized in that, The upper paving layer includes 120-130 parts fine aggregate, 12-15 parts limestone powder, 3-5 parts basalt fiber, 16-20 parts modified asphalt, and 25-30 parts Wenlun rubber mixture. The waterproof bonding layer includes 50-60 parts modified asphalt, 15-18 parts epoxy resin, 1-2 parts silane coupling agent, 3-4 parts curing agent, 0.5-0.8 parts curing accelerator, 3-6 parts styrene-butadiene rubber, and 4-7 parts talc. The lower paving layer includes 150-160 parts coarse aggregate, 10-15 parts modified asphalt, 30-40 parts acrylonitrile-butadiene-styrene copolymer, 20-23 parts porous ceramic microparticles, 6-10 parts rubber granules, 8-12 parts calcium stearate, and 13-16 parts waterborne polyurethane.

3. The high-viscosity asphalt double-layer SMA pavement structure according to claim 1, characterized in that, The preparation method of the Wenlun rubber compound includes the following steps: (1) Disperse Wenlun collagen powder in deionized water, add magnesium aluminum silicate, nano titanium dioxide and sodium hydroxide solution, stir at 35-40℃ for 20-25 min, dry, grind to obtain pretreated Wenlun collagen; (2) Disperse the coconut shell mixture in deionized water, add the pretreated Wenlun gum, ferrous sulfate solution and soybean gum from step (1), stir at 50-55℃ for 1-2 hours, and dry to obtain Wenlun gum mixture.

4. The high-viscosity asphalt double-layer SMA pavement structure according to claim 3, characterized in that, The mass ratio of the Wenlun collagen powder, coconut shell mixture, and soybean gum is 1:0.6-0.7:0.2-0.

3.

5. The high-viscosity asphalt double-layer SMA pavement structure according to claim 3, characterized in that, The preparation method of the coconut shell mixture includes the following steps: crushing coconut shells, drying them, dispersing them in citric acid, stirring for 10-15 min, washing them with water, dispersing them again in deionized water, adding silane coupling agent modified chitosan microspheres, microporous activated carbon, and rosin extract, stirring at 160-180 r / min for 1-2 h at room temperature, drying them, ball milling them, and sieving them to obtain the coconut shell mixture; The method for preparing chitosan microspheres modified with silane coupling agent includes the following steps: dispersing chitosan in acetic acid solution, adding epichlorohydrin and sodium tripolyphosphate to obtain a pre-crosslinked material, dispersing the pre-crosslinked material in silicone oil, adding an emulsifier, spray drying, washing with n-hexane to obtain microspheres, dispersing the microspheres in an aqueous solution of silane coupling agent, stirring for 1-2 hours, filtering, and obtaining chitosan microspheres modified with silane coupling agent.

6. The high-viscosity asphalt double-layer SMA pavement structure according to claim 1, characterized in that, The method for preparing the porous ceramic microparticles includes the following steps: (1) Ceramic powder, nano-calcium carbonate and nano-clay are dispersed in deionized water to obtain a slurry, which is then spray-dried to obtain porous particles; (2) Disperse starch-coated lignin particles in butanone, add the porous particles, polytetrafluoroethylene powder and alicyclic polyamine from step (1), stir at 70-75℃ for 1-2 hours, filter, wash with water, and dry to obtain porous ceramic microparticles.

7. The high-viscosity asphalt double-layer SMA pavement structure according to claim 6, characterized in that, The mass ratio of the ceramic powder, starch-coated lignin particles, and polytetrafluoroethylene powder is 1:0.4-0.5:0.08-0.

09.

8. The high-viscosity asphalt double-layer SMA pavement structure according to claim 6, characterized in that, The method for preparing starch-coated lignin particles includes the following steps: dispersing lignin in ethylene glycol, adding disodium lauryl sulfosuccinate monoester and carbon nanotubes, and then subjecting the mixture to ultrasonic treatment and freeze-drying to obtain lignin particles. Lignin particles were dispersed in a starch aqueous solution, sodium trimetaphosphate and sodium hydroxyphosphate were added, and the mixture was stirred at 75-80℃ for 30-35 minutes and then dried to obtain starch-coated lignin particles.

9. The high-viscosity asphalt double-layer SMA pavement structure according to claim 1, characterized in that, The fine aggregate is river sand with a particle size of 5-8 mm, and the coarse aggregate is basalt crushed stone with a particle size of 14-18 mm.

10. The construction method of a high-viscosity asphalt double-layer SMA pavement structure according to claim 1, characterized in that, Includes the following steps: (1) Mix fine aggregate, limestone powder, modified asphalt, basalt fiber and Wenlun rubber mixture to obtain the upper paving mixture; (2) Mix modified asphalt, epoxy resin, silane coupling agent, curing agent, curing accelerator, styrene-butadiene rubber and talc to obtain a waterproof adhesive; (3) Mix coarse aggregate, acrylonitrile-butadiene-styrene copolymer, modified asphalt, porous ceramic microparticles, rubber particles, calcium stearate and waterborne polyurethane to obtain the underlay mixture; (4) Lay the lower mixture flat and compact it, then apply waterproof adhesive, then lay the upper mixture flat and compact it, and cure for 20-24 hours to obtain a high viscosity asphalt double-layer SMA pavement structure.